The Cyclosporine-A Treatment does not have Harmful Effect on the Linear Growth of Pediatric Patients with Steroid-dependent and Steroid-resistant Nephrotic Syndrome - Sang Soo Lee; Ji Hoon Kim; Chung Ho Kim; Byoung-Soo Cho; Deog Yoon Kim; Il Ki Hong; Jin-Soon Suh (Korean Society of Pediatric Nephrology, 2016)
Purpose This study was performed to evaluate the effects of cyclosporine-A (CsA) on linear growth in pediatric patients with steroid-dependent (SDNS) or resistant nephrotic syndrome (SRNS). Methods Thirty-five pediatric patients with SDNS or SRNS undergoing glucocorticoid (GC) and/or CsA treatment were retrospectively reviewed. Seventeen patients were treated with GC alone and 18 were treated with GC and CsA. The cumulative doses of GC and CsA were quantified (mg/kg/day). Linear growth during the follow-up period was defined as the difference in Z-score between the initial and final height according to the follow-up period (Δ height Z score/year). The associations between linear growth and clinical parameters were analyzed. Results The linear growth of patients in the two groups was not significantly different (P =0.262). The Δ height Z score/year did not show a significant correlation with the cumulative doses of CsA, but was negatively correlated with the cumulative dose of GC and positively correlated with the Z score for height at the time of diagnosis. Conclusion In children with SDNS or SRNS undergoing GC therapy, added CsA treatment may not have harmful effects on linear growth.